2020
DOI: 10.1002/ajmg.a.61580
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic expansion of Bosch–Boonstra–Schaaf optic atrophy syndrome and further evidence for genotype–phenotype correlations

Abstract: Bosch-Boonstra-Schaaf Optic Atrophy Syndrome (BBSOAS) is an autosomal dominant neurodevelopmental disorder caused by loss-of-function variants in NR2F1 and characterized by visual impairment, developmental delay, and intellectual disability.Here we report 18 new cases, provide additional clinical information for 9 previously reported individuals, and review an additional 27 published cases to present a total of 54 patients. Among these are 22 individuals with point mutations or in-frame deletions in the DNA-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 49 publications
(65 reference statements)
0
60
0
Order By: Relevance
“… 7 The most common neuroanatomical malformation found in patients with ONH is hypoplasia of the corpus callosum associated with developmental delay, neurological deficits and seizures, 6 , 34 which are all clinical features observed in children carrying disease-causing NR2F1 variants. 16 , 19 In addition, ONH is characterized by congenital deficiency of RGCs and their axons, which lead to disorganization of the GCL, RNFL thinning, and a small optic disc with a thin optic nerve. Various theories have been proposed to explain the aetiology of ONH, including a developmental failure of RGCs.…”
Section: Discussionmentioning
confidence: 99%
“… 7 The most common neuroanatomical malformation found in patients with ONH is hypoplasia of the corpus callosum associated with developmental delay, neurological deficits and seizures, 6 , 34 which are all clinical features observed in children carrying disease-causing NR2F1 variants. 16 , 19 In addition, ONH is characterized by congenital deficiency of RGCs and their axons, which lead to disorganization of the GCL, RNFL thinning, and a small optic disc with a thin optic nerve. Various theories have been proposed to explain the aetiology of ONH, including a developmental failure of RGCs.…”
Section: Discussionmentioning
confidence: 99%
“…Among NDDs, a recently described genetic condition called Bosch-Boonstra-Schaff Optic Atrophy Syndrome (BBSOAS) has been first reported in 2014 (Bosch et al, 2014 ). Till now, about 100 patients have been diagnosed (Rech et al, 2020 ), but more cases are regularly identified worldwide, indicating that the prevalence of this new syndrome is still, most probably, underestimated. BBSOAS symptoms are very heterogeneous and combine, among others, intellectual deficits, global developmental delay, epilepsy, motor dysfunctions and autistic traits, often associated with optic nerve atrophy and cerebral visual impairment.…”
Section: Introductionmentioning
confidence: 99%
“…BBSOAS is caused by NR2F1 haploinsufficiency, implying that all patients so far identified carry a non-functional NR2F1 allele, either due to deletion or missense point mutations that compromise its expression levels and/or its molecular activity. Although reported mainly as de novo mutations, a few BBSOAS inherited variants have been recently described (Rech et al, 2020 ; Jurkute et al, 2021 ). The BBSOAS causative gene - NR2F1 - and its homolog NR2F2 code for transcriptional regulators belonging to the superfamily of steroid/thyroid hormone receptors.…”
Section: Introductionmentioning
confidence: 99%
“…This, together with the difficulty of obtaining high‐resolution magnetic resonance imaging (MRI) at young age, has limited the investigation of possible brain malformations, which could correlate with the high frequency of ID (more than 80%) and epileptic seizures (40%) in BBSOAS patients. New reports are constantly expanding the BBSOAS clinical spectrum (Chen et al , ; Martín‐Hernández et al , ; Bojanek et al , ; Park et al , ; Rech et al , ), as more patients are identified and the pathophysiology of different brain regions or different organs starts to be explored.…”
Section: Introductionmentioning
confidence: 99%